Differential Protective Efficacy of DNA Vaccines Expressing Secreted Proteins of Mycobacterium tuberculosis - Kamath, Arun T. (American Society for Microbiology, 1999)
The development of more-effective antituberculosis vaccines would assist in the control of the global problem of infection with Mycobacterium tuberculosis. One recently devised vaccination strategy is immunization with DNA plasmids encoding individual microbial genes. Using the genes for the M. tuberculosis secreted proteins MPT64 (23 kDa), Ag85B (30 kDa), and ESAT-6 (6 kDa) as candidate antigens, DNA vaccines were prepared and tested for immunogenicity and protective efficacy in a murine model of aerosolized tuberculosis (TB). Intramuscular immunization with DNA-64 or DNA-85B resulted in the activation of CD4(+) T cells, which produce gamma interferon (IFN-γ), and high titers of specific immunoglobulin G antibodies. Further, DNA-64 induced major histocompatibility complex class I-restricted CD8(+) cytotoxic T cells. The addition of a eukaryotic leader sequence to mpt64 did not significantly increase the T-cell or antibody response. Each of the three DNA vectors stimulated a significant reduction in the level of M. tuberculosis infection in the lungs of mice challenged 4 weeks after immunization, but not to the levels resulting after immunization with Mycobacterium bovis BCG. The vaccines showed a consistent hierarchy of protection, with the most effective being Ag85B, followed by ESAT-6 and then MPT64. Coimmunization with the three vectors resulted in a greater degree of protection than that induced by any single vector. This protective efficacy was associated with the emergence of IFN-γ-secreting T cells earlier than in infected animals immunized with a control vector. The efficacy of these DNA vaccines suggests that multisubunit vaccination may contribute to future vaccine strategies against TB.